Contrast‐enhanced sonographic appearances of two primary hepatic epithelioid angiomyolipomas. Issue 5 (3rd February 2020) - Chai, Victor; Fox, Adrian; Chong, Lynn; House, Eloise; Sutherland, Tom
Abstract: Epithelioid hepatic angiomyolipoma (Epi‐HAML) is a rare hepatic tumor frequently misdiagnosed as hepatocellular carcinoma (HCC). Unlike conventional angiomyolipoma (AML), Epi‐HAML contains minimal amount of adipose tissue, which is a radiological distinguishing feature between AML and HCC. Two patients were referred for management of incidentally found hepatic lesions confirmed to be Epi‐HAML on post‐resection tissue analysis. CT and MRI findings were suggestive of HCC. Contrast‐enhanced ultrasound demonstrated intratumoral shunting, a feeding artery, and early draining hepatic vein. These findings should alert radiologists to the possibility of Epi‐HAML. Furthermore, these features may be better assessed by contrast‐enhanced ultrasound due to its superior dynamic temporal resolution.